IoT‐Based Elderly Health Monitoring System Using Firebase Cloud Computing - Adhan Efendi; Muhammad Imam Ammarullah; Indra Griha Tofik Isa; Meli Puspita Sari; Jasmine Nurul Izza; Yohanes Sinung Nugroho; Hamid Nasrullah; Denny Alfian (Health Science Reports)
ABSTRACT Background and Aims The increasing elderly population presents significant challenges for healthcare systems, necessitating innovative solutions for continuous health monitoring. This study develops and validates an IoT‐based elderly monitoring system designed to enhance the quality of life for elderly people. The system features a robust Android‐based user interface integrated with the Firebase cloud platform, ensuring real‐time data collection and analysis. In addition, a supervised machine learning technology is implemented to conduct prediction task of the observed user whether in “stable” or “not stable” condition based on real‐time parameter. Methods The system architecture adopts the IoT layer including physical layer, network layer, and application layer. Device validation is conducted by involving six participants to measure the real‐time data of heart‐rate, oxygen saturation, and body temperature, then analysed by mean average percentage error (MAPE) to define error rate. A comparative experiment is conducted to define the optimal supervised machine learning model to be deployed into the system by analysing evaluation metrics. Meanwhile, the user satisfaction aspect evaluated by the terms of usability, comfort, security, and effectiveness. Results IoT‐based elderly health monitoring system has been constructed with a MAPE of 0.90% across the parameters: heart‐rate (1.68%), oxygen saturation (0.57%), and body temperature (0.44%). In machine learning experiment indicates XGBoost model has the optimal performance based on the evaluation metrics of accuracy and F1 score which generates 0.973 and 0.970, respectively. In user satisfaction aspect based on usability, comfort, security, and effectiveness achieving a high rating of 86.55%. Conclusion This system offers practical applications for both elderly users and caregivers, enabling real‐time monitoring of health conditions. Future enhancements may include integration with artificial intelligence technologies such as machine learning and deep learning to predict health conditions from data patterns, further improving the system's capabilities and effectiveness in elderly care.